Leukocytoclastic vasculitis in a child with epidermolysis bullosa simplex - Sezgin, Gülay; Ceyhan, Mehmet; Seçmeer, Gülten; Bakkaloğlu, Ayşın; Kanra, Güler; Büyükkale, Gökhan (The Turkish Journal of Pediatrics, 1999)
A 10-year-old boy with epidermolysis bullosa simplex (Weber-Cockayne variant) together with leukocytoclastic vasculitis is presented. He was admitted to the hospital with the provisional diagnoses of infected epidermolysis bullosa simplex or drug eruption. On the sixth day of hospitalization he developed palpable purpura, abdominal pain and bloody diarrhea, together with hematuria and proteinuria. A generalized tonic-clonic convulsion, changes in mental status, fluctuations in arterial blood pressure and intractable pain in his extremities occurred during the course of hospitalization. Systemic pulse steroid therapy, antibiotics, and antihypertensive and anticonvulsive drugs were given. On the 30th day of hospitalization, a skin graft was performed to replace a large tissue defect on his left hand. Despite high dose steroid therapy, his hematuria, proteinuria and hypertension continued after his discharge, suggesting a steroid-resistant renal pathology, such as focal glomerulosclerosis, that occurred secondary to leukocytoclastic vasculitis.